Between the Great Patriotic War and World War II: the Image of the War in Ukrainian Feature Films after 1991 - Gontarska, Olga (Institute of National Remembrance Review, 2021)
The article focuses on the examples of Ukrainian historical feature films set in World War II and the so-called “war after the war” in Ukraine. The images considered evade rigid categories, and show the diversity of cultural representations of the period in question, which constitute a field of negotiation between the narrative of the Great Patriotic War and World War II. Film images will be analysed as a historical sources for study of the perceptions of history. The article’s main goal is to answer the question of “whose history” is presented there. The text is intended to present the films as the result of the activities of the various actors involved in politics of history in its broad definition.